THE ROLE AND PROSPECTS OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN MODERN LEXICOGRAPHY (International journal of artificial intelligence, 2025)
This article analyzes the role and significance of artificial intelligence (AI) technologies in modern lexicography. The development of electronic dictionaries, corpus linguistics, machine learning, and natural language processing (NLP) technologies has laid the foundation for automating lexicographic processes. The research highlights the necessity of creating a lexicographic database for the Uzbek language, particularly its role in translation systems. Furthermore, based on the analysis of foreign experiences, the article outlines the prospects for developing AI-based interactive dictionary platforms for the Uzbek language.